1993
DOI: 10.1207/s15327752jpa6003_2
|View full text |Cite
|
Sign up to set email alerts
|

Children's Affective Reactions and Coping Under Threat of Missile Attack: A Semiprojective Assessment Procedure

Abstract: This study reports on 170 Israeli school children at risk for missile attack during the Persian Gulf War. The Bar-Ilan Picture Test for Children (Itskowitz & Strauss, 1982, 1986) was specially adapted to the war situation specifically to measure children's affective reactions and coping strategies. Children with a greater sense of control and social support, and more complex defenses, tended to demonstrate better coping strategies. Children who were less defensive showed higher levels of anxiety under stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
1
16
0
3
Order By: Relevance
“…Maternal PTSD correlates with child's PTSD (Thabet et al . 2008), and maternal anxiety correlates with child anxiety (Zeidner & Klingman 1993). Behavioural problems were associated with living with a divorced/single parent and having less than two siblings (Farbstein et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal PTSD correlates with child's PTSD (Thabet et al . 2008), and maternal anxiety correlates with child anxiety (Zeidner & Klingman 1993). Behavioural problems were associated with living with a divorced/single parent and having less than two siblings (Farbstein et al .…”
Section: Resultsmentioning
confidence: 99%
“…Stress was negatively correlated with supportive family and positively correlated with parents', friends' and others' stress (Shamai & Kimhi 2007). Maternal PTSD correlates with child's PTSD (Thabet et al 2008), and maternal anxiety correlates with child anxiety (Zeidner & Klingman 1993). Behavioural problems were associated with living with a divorced/single parent and having less than two siblings (Farbstein et al 2010).…”
Section: Protective Factorsmentioning
confidence: 99%
“…As a variable, gender can affect the way in which individuals manifest stress outcomes. Results of various studies indicated the presence of gender differences, with women generally reporting a higher level of stress (Brimblecombe & Ormston, 1996;De-Anda, Bradley, & Collada, 1997;Zeidner, Klingman, & Itskowitz, 1993) and greater social support (Reevy & Maslach, 2001) than do men. Lee, Keough, and Sexton (2002), who examined the effects of social appraisal of the campus climate and perceived stress of college women and men, found that social connectedness was more negatively related to perceived stress for men than for women.…”
Section: Stressorsmentioning
confidence: 99%
“…Gender differences in anxiety and stress reactions were consistent with the vast literature on this complex question (Maccoby & Jacklin, 1976). Girls and women reported higher levels of war-related distressful reactions (e.g., fear, anxiety, physical complaints) and behavior problems than boys and men, and as a consequence showed more interest in individual and group counseling (Ben-Zur & Zeidner, 1991;Greenbaum et al, 1993;Keinan, 1992;Klingman & Goldstein, 1992;Mintz, 1992;Rahav & Ronen, 1993;Rosenbaum & Ben-Yoseff, 1993;Rosenbaum & Ronen, 1993;Toubiana et al, 1992;Zeidner, Klingman, & Itzkovits, 1993). These studies did not attempt to investigate why this was so and offered explanations based (1) on sex-linked propensities and or gender-related socialization practices affecting degree of affective arousal, (2) on situation-specific stress sensitivity and willingness to acknowledge personal distress, and (3) on prior gender-specific experiences with war-related stressors.…”
Section: Demographic Variablesmentioning
confidence: 99%
“…This finding is similar to the social referencing phenomena in infants and young children (Klinnert et al, 1983). Analyses of children's stories in a semiprojective assessment procedure described below (Zeidner et al, 1993) revealed a strong relationship between the level of perceived anxiety in children, their age peers, and their parents in these stories. Israelshvili (1992) also found strong relationships between adolescents' ratings of their anxiety levels and self-confidence in coping with war-related stressors and their ratings of their family and classmates on these variables.…”
Section: The Affective Effect Of Children's Perceptions Of Parents' Amentioning
confidence: 99%